GAMBARAN ASAM URAT PADA REMAJA OBES DI KABUPATEN MINAHASA - Wurangian, Vindy G. N. (e-Biomedik, 2014)
Abstract: Uric acid is an end product of purine metabolism and is also associated with obesity. Most people with this condition are overweight and have a tendency of hyperuricemia which is associated with insulin resistance. Insulin resistance is the basis of metabolic abnormalities that could explain the relationship between the various components of the metabolic syndrome. This study aimed to determine the profile of uric acid in obese adolescent.This was a descriptive study with cross sectional design. Sampling technique used was random sampling method. Samples consisted of obese students determined by measuring their waist circumferences. The students had to fast for at least 8 hours, and then their blood was taken for examination of blood uric acid level. The results showed that there were 54 obese students as samples, and 8 students (14.28%) with hyperuricemia. Of those with hyperuricemia, there were 3 male students (5.56%) and 5 female students (9.26%). Conclusion: Although a large part of obese students in Minahasa had normal blood uric acid levels, some of them showed hyperuricemia.Keywords: uric acid, hyperuricemia, obeseAbstrak: Asam urat merupakan hasil akhir metabolisme purin. Asam urat sering dikaitkan dengan obesitas. Orang dengan kegemukan mempunyai kecenderungan mengalami peningkatan kadar asam urat dalam darah. Asam urat berhubungan dengan resistensi insulin. Resistensi insulin merupakan dasar kelainan metabolik yang dapat menjelaskan hubungan antara berbagai komponen sindrom metabolik. Penelitian ini bertujuan untuk mengetahui gambaran asam urat pada remaja obes. Penelitian ini bersifat deskriptif dengan desain potong lintang. Sampel diperoleh dengan tekhnik random sampling. Sebagai sampel penelitian diambil siswa-siswi SMK Negeri Tondano yang obes yang ditentukan berdasarkan lingkar pinggang. Siswa yang bersedia dijadikan sampel diminta untuk berpuasa minimal 8 jam, kemudian diambil darahnya untuk pemeriksaan kadar asam urat. Hasil penelitian memperlihatkan dari 54 siswa obes diperoleh prevalensi siswa obes yang mengalami hiperurisemia di Kabupaten Minahasa 8 orang (14,82%), yang terdiri dari 3 siswa laki-laki (5,56%) dan 5 siswa perempuan (9,26%). Simpulan: Walaupun sebagian besar siswa obes mempunyai kadar asam urat darah yang normal, beberapa di antaranya memperlihatkan hiperurisemia.Kata kunci: asam urat, hiperurisemia, obesitas